Optimal Municipal Cash Management: A Case Study - Maldonado, Rita M.; Ritter, Lawrence S. (The Review of Economics and Statistics, 1971)
Less extreme cases, however, are even more worrisome, primarily because the distortions in the solutions are less easy to identify. As shown above, (Nim)1 and (N1m) 2 without distortions differ in this illustration by 20 per cent of their mean value. WYhile it is easy to flag this difference for a steady series like labor force, there are many series, e.g., inventory investment, for which a 20 per cent jump is nothing to cause surprise. Further, if the relevant